Strategi Pengembangan Kapasitas Perawat Gigi Dalam Pelayanan Kesehatan Gigi di Rumah Sakit Gigi Mulut Pendidikan Nala Husada Universitas Hang Tuah - Anita Yuli Puspitasari; Dewi Casmiwati (Faculty of Social and Political Science, 2025)
In current conditions there are a number of diseases and disorders, one of which is dental and oral disease. Because these diseases and health disorders require special treatment, a strategy is needed to develop the capacity of dental nurses. The ability, skills and attitudes of dental nurses' professionalism and accountability for the implementation of health services need to be improved in terms of professionalism. With the aim of studying and explaining how the strategy for developing the capacity of dental nurses in dental health services at RSGMP Nala Husada, to develop a strategy to increase efficiency, effectiveness, and responsiveness. Using a qualitative research method that describes and studies the strategy for developing the capacity of dental nurses in dental health services at RSGMP Nala Husada. The research approach uses a case study approach, with data collection techniques through observation, interviews, and documentation. The results and conclusions that the strategy for developing the capacity of dental nurses in dental and oral health services at RSGMP Nala Husada is quite good in the HR Dimension of Working Conditions & Recruitment, the Dimension of Organizational Development in the Incentive System, HR Utilization, Leadership, Organizational Culture & Communication and Institutional Reform in the Regulatory Framework that covers it. However, it still needs to be improved in terms of training programs for dental nurses, because these training activities are not held routinely, to be able to follow the training only according to the needs required in each service unit at RSGMP Nala Husada. For this reason, it is necessary to improve additional training programs for dental nurses to develop a strategy to improve efficiency, effectiveness, and responsiveness so that the quality of dental and oral health services at RSGMP Nala Husada is even better and more satisfying for patients.